Surface Proteins of Lactococcus lactis: Bacterial Resources for Muco-adhesion in the Gastrointestinal Tract - Mercier-Bonin, Muriel; Chapot-Chartier, Marie-Pierre (Frontiers in Microbiology, 2017)
Food and probiotic bacteria, in particular lactic acid bacteria (LAB), are ingested in large amounts by humans and are part of the transient microbiota which is increasingly considered to be able to impact the resident microbiota and thus possibly the host health. The lactic acid bacterium Lactococcus lactis is extensively used in starter cultures to produce dairy fermented food. Also because of a generally recognized as safe (GRAS) status, L. lactis has been considered as a possible vehicle to deliver in vivo therapeutic molecules with anti-inflammatory properties in the gastro-intestinal tract. One of the key factors that may favor health effects of beneficial bacteria to the host is their capacity to colonize transiently the gut, notably through close interactions with mucus, which covers and protects the intestinal epithelium. Several L. lactis strains have been shown to exhibit mucus-binding properties and bacterial surface proteins have been identified as key determinants of such capacity. In this review, we describe the different types of surface proteins found in L. lactis, with a special focus on mucus-binding proteins and pili. We also review the different approaches used to investigate the adhesion of L. lactis to mucus, and particularly to mucins, one of its major components, and we present how these approaches allowed revealing the role of surface proteins in muco-adhesion.